Remaining Service Life Struktur Conveyor J pada Tambang Batubara PT GHI di Kabupaten Tapin Provinsi Kalimantan Selatan - Ajeng Agustina Natahsia; Elfida Moralista; Zaenal (UNISBA Press, 2023)
Abstract. Conveyor is one of the means of transportation used in the mining industry, both to move excavated material processing and mining activities. The Conveyor structure is made of carbon steel material with strong structural characteristics and is susceptible to corrosion to oxidation due to environmental factors. With the occurrence of corrosion, it can cause damage and reduce the Remaining Service Life of the Conveyor structure. This study was conducted to determine Remaining Service Life, Corrosion Rate, type of corrosion and corrosion control on Conveyor structures. This study uses methodology measurement of thickness reduction of Conveyor structure. The actual thickness measurement on the Conveyor structure has a length of 94 meters divided into 3 segments with 25 test points above ground level. The tool used in measuring the thickness of the Conveyor structure is Ultrasonic Thickness Gauge TT 130.The type of corrosion that occurs in this Conveyor structure is evenly distributed corrosion. The method used for corrosion control is the Coating method with a three-layer system using Primer Coating Seaguard 5000, Intermediate Coating Sherglas FF and Top Coating Aliphatic Acrylic Modified Polyurethane. The value of Corrosion Rate that occurs in Conveyor structures ranges from 0.1814 – 0.3042 mm/year including the “good” category based on the relative corrosion resistance of steel. As for the design life of the Conveyor structure, which is 15 years and the remaining service life is 7 years, based on the calculation results obtained from the Remaining Service Life value it ranges from 6.71 – 9.65 years. Thus, 9 out of 25 test points or 36% were predicted to be unable to reach the predetermined design life of 15 years. Abstrak. Conveyor merupakan salah satu alat angkut yang digunakan dalam industri pertambangan, baik untuk memindahkan material pengolahan bahan galian maupun aktivitas penambangan. Struktur Conveyor terbuat dari material baja karbon dengan karakteristik struktur yang kuat serta rentan mengalami korosi terhadap oksidasi akibat dari faktor lingkungannya. Dengan terjadinya korosi maka dapat mengakibatkan kerusakan serta mengurangi Remaining Service Life pada struktur Conveyor. Penelitian ini dilakukan untuk mengetahui Remaining Service Life, Corrosion Rate, jenis korosi dan pengendalian korosi pada struktur Conveyor. Pada penelitian ini menggunakan metodologi pengukuran pengurangan ketebalan struktur Conveyor. Pengukuran tebal aktual pada struktur Conveyor memiliki panjang 94 meter yang dibagi menjadi 3 segmen dengan 25 test point yang berada di atas permukaan tanah. Alat yang digunakan dalam pengukuran ketebalan struktur Conveyor yaitu Ultrasonic Thickness Gauge TT 130. Jenis korosi yang terjadi pada struktur Conveyor ini ialah korosi merata. Metode yang digunakan untuk pengendalian korosi ialah metode Coating dengan sistem three layer menggunakan Primer Coating Seaguard 5000, Intermediate Coating Sherglas FF dan Top Coating Aliphatic Acrylic Modified Polyurethane. Nilai Corrosion Rate yang terjadi pada struktur Conveyor berkisar antara 0,1814 – 0,3042 mm/tahun termasuk kategori “good”dengan berdasarkan ketahanan korosi relatif baja. Sedangkan untuk umur desain dari struktur Conveyor yaitu 15 tahun dan umur sisa pakai 7 tahun, berdasarkan dari hasil perhitungan yang diperoleh dari nilai Remaining Service Life itu berkisar 6,71 – 9,65 tahun. Dengan demikian di dapatkan hasil sebanyak 9 dari 25 test point atau 36% yang diprediksi tidak dapat mencapai umur desainnya yang telah ditentukan yaitu 15 tahun.